Deciphering the pathogenic role of rare RAF1 heterozygous missense mutation in the late-presenting DDH - Liu, Yuzhao; Fan, Xuesong; Qian, Kun; Wu, Changshun; Zhang, Laibo; Yuan, Lin; Man, Zhentao; Wu, Shuai; Li, Ping; Wang, Xianquan; Li, Wei; Zhang, Yuanqing; et al. (Frontiers in Genetics, 2024)
Background Developmental Dysplasia of the Hip (DDH) is a skeletal disorder where late-presenting forms often escape early diagnosis, leading to limb and pain in adults.The genetic basis of DDH is not fully understood despite known genetic predispositions.We employed Whole Genome Sequencing (WGS) to explore the genetic factors in late-presenting DDH in two unrelated families, supported by phenotypic analyses and in vitro validation. Results In both cases, a novel de novo heterozygous missense mutation in RAF1 (c.193A>G [p. Lys65Glu]) was identified. This mutation impacted RAF1 protein structure and function, altering downstream signaling in the Ras/ERK pathway, as demonstrated by bioinformatics, molecular dynamics simulations, and in vitro validations. Conclusion This study contributes to our understanding of the genetic factors involved in DDH by identifying a novel mutation in RAF1. The identification of the RAF1 mutation suggests a possible involvement of the Ras/ERK pathway in the pathogenesis of late-presenting DDH, indicating its potential role in skeletal development.